Investigação de aspectos cognitivos e morais do desenvolvimento por meio de um conto de fadas: um estudo a partir do referencial piagetiano - Seabra, Silvia Lorenzoni Perim (2015)
Studies on child development in their cognitive and moral aspects are recurring in researches with children. Jean Piaget's perspective of genetic epistemology assumes that there is an evolution of such aspects during childhood. In the research with children, fairy tales show up as a tool that arouse their interest, with which they identify themselves and how they are able to position themselves in relation to the content of the tale. Such tool is characterized as a privileged way to access representations and explanations of the reality that children of different ages have. This research aimed to study aspects of cognitive and moral development of children through a fairy tale. The participants were 24 boys and girls aged 6/7 and 10/11 that, after having access to the fairy tale "Hansel and Gretel" in multimedia version, were asked to reconstruct the story and answered to an interview based on the Piaget clinical method. The idea of employing the fairy tale as a child development study tool proved to be very interesting and valid, since the answers given by the children expressed their way of thinking, denoted their mental organization and how they see the world. The results related to cognitive aspects pointed out that most children reconstructs the tale within the concrete way, and in the aspect of moral development most children presents a more heteronomous position to judge the actions of the characters. Such results reinforced the Piagetian idea of cognitive and moral development evolution throughout the childhood, enabled investigate the thought structure and language of children of the age groups studied, and open possibility of expanding the ages researched and details of part of the study concerning the moral aspect.